2020
DOI: 10.1371/journal.pone.0237015
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B as a therapeutic target for Graves’ orbitopathy in an in vitro model

Abstract: Graves’ orbitopathy (GO) is characterised in early stages by orbital fibroblast inflammation, which can be aggravated by oxidative stress and often leads to fibrosis. Protein tyrosine protein 1B (PTP1B) is a regulator of inflammation and a therapeutic target in diabetes. We investigated the role of PTP1B in the GO mechanism using orbital fibroblasts from GO and healthy non-GO subjects. After 24 hours of transfection with PTPN1 siRNA, the fibroblasts were exposed to interleukin (IL)-1β, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…Our study with siRNA transfection is limited by the lack of mRNA data, which would have provided additional insights to its effect at transcriptional or translational level. However, like other studies that have employed similar methods ( 53 , 54 ), we believe that we have shown a concrete evidence with western blot and ELISA that PCSK9, regardless of the mechanism with which its level is modified, affects inflammation and adipogenesis in GO. In line with our study, Kumar et al.…”
Section: Discussionsupporting
confidence: 83%
“…Our study with siRNA transfection is limited by the lack of mRNA data, which would have provided additional insights to its effect at transcriptional or translational level. However, like other studies that have employed similar methods ( 53 , 54 ), we believe that we have shown a concrete evidence with western blot and ELISA that PCSK9, regardless of the mechanism with which its level is modified, affects inflammation and adipogenesis in GO. In line with our study, Kumar et al.…”
Section: Discussionsupporting
confidence: 83%
“…Our study with siRNA transfection is limited by the lack of mRNA data, which would have provided additional insights to its effect at transcriptional or translational level. However, like other studies that have employed similar methods (53,54), we believe that we have shown a concrete evidence with western blot and ELISA that PCSK9, regardless of the mechanism with which its level is modified, affects inflammation and adipogenesis in GO. In line with our study, Kumar et al have previously reported that an autoantibody against TSH receptor stimulated the phosphoinositide 3-kinase (PI3K)/Akt pathway and induced adipogenesis of orbital preadipocytes in GO (55).…”
Section: Discussionsupporting
confidence: 79%
“…PTP1B inhibition suppressed IL-1binduced Akt, and JNK phosphorylation, but p38 MAPK phosphorylation was reduced only in GO OF. As the p38 and JNK pathways, and the MAPK pathway, can mediate the transcription and translation of inflammatory cytokines, this study demonstrated that PTP1B mediates inflammatory reactions in GO OF (76).…”
Section: Cytokines In Gd and Gomentioning
confidence: 58%
“…Systemic hyperthyroidism and T cell infiltration into orbital tissue leads to ROS production, which can aggravate GO severity by increasing T cell proliferation, adipogenesis, and GAG production in OF (75). Recently, the role of the protein tyrosine phosphatase 1B (PTP1B), encoded by the PTPN1 gene, has been characterized in GO (76). PTP1B is known to be involved in immune cell signaling by regulating cytokines via dephosphorylation of janus kinase (JAK)2, signal transducer and activator of transcription (STAT)5, and tyrosine kinase (TYK)2.…”
Section: Cytokines In Gd and Gomentioning
confidence: 99%